Supply Chain Management Model and the Profitability of Major Pharmaceutical Companies in Peru - Torres Cáceres, Nolberto (2020)
This article proposes that the use of a management model in the main pharmaceutical companies in Peru favors supply chain management and profitability. Interest in this study arises from the concern about health risk due to the shortage of medicines; therefore, it attempts to solve this problem by applying the supply chain management model, as improved profitability means having greater access to medicines for the Peruvian population. This study provides information on the importance of strengthening the provision of services in medicine distribution through optimal management of health supplies. The analysis is based on five companies in this sector. The results indicate that the administration described promises an immediate improvement.